KEPENTINGAN INDONESIA DALAM PENANGANAN RED NOTICE INTERPOL PHO HOCH KENG - Purnayuda, Sukma Teja; Wahyudi, Fendy Eko; Susiatiningsih, Hermini (Journal of International Relations, 2015)
Sport in 21st century poses many threats, such as doping scandal,underage player transfer, and sport corruption. Match-fixing is oneof sport manipulation examples, also commonly known as sportfixing.The detrimental effect of match-fixing to sport industry hasraised the urgency of international police cooperation, because ofthe transnational nature of this crime. The type of research used inthis research is explanative, aiming to explain the connectionbetween variable. The variable is cooperation between IndonesiaInterpol and Italy Interpol, with background fact that Indonesia hasnot set the law regarding match-fixing crime yet. This research triesto explain why Indonesia is willing to cooperate with Italy to handlePho Hoch Keng case. The result from this research are in theimplementation of cooperation, Indonesia is not only looking formaterial benefit from the cooperation, but also maintainingreputation of the state.